2012
DOI: 10.1159/000338696
|View full text |Cite
|
Sign up to set email alerts
|

Variegated Dermoscopy of in situ Melanoma

Abstract: Background: Melanomas in situ (MIS) are difficult to diagnose, lacking well-established dermoscopic descriptors. Objective: The aim of this study was toimprove the identification of early melanomas describing the variegated dermoscopic features of MIS and their correlation with demographic and clinical aspects. Methods: Dermoscopic images of 114 histologically proven MIS were evaluated by 3 expert dermoscopists and classified into their main dermoscopic patterns. Dermoscopic features were also considered for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 51 publications
(35 reference statements)
10
36
0
Order By: Relevance
“…This was highlighted in a recent study describing eight novel dermoscopic patterns of in situ melanoma. The authors postulated that the morphologic diversity might reflect a variability in origin or biologic behavior of the tumor [15]. Some of the traditional algorithms have been accordingly modified to a lower threshold for excision of lesions showing only one of the classic criteria that, if prominent, may be judged enough to warrant excision [16].…”
Section: Use the 10 Seconds Rule In Single Lesionsmentioning
confidence: 99%
“…This was highlighted in a recent study describing eight novel dermoscopic patterns of in situ melanoma. The authors postulated that the morphologic diversity might reflect a variability in origin or biologic behavior of the tumor [15]. Some of the traditional algorithms have been accordingly modified to a lower threshold for excision of lesions showing only one of the classic criteria that, if prominent, may be judged enough to warrant excision [16].…”
Section: Use the 10 Seconds Rule In Single Lesionsmentioning
confidence: 99%
“…globular-homogeneous and multicomponent (when reticular, globular, and homogeneous areas were all found within the same lesion) (12,13). Other patterns observed in our study were the starburst pattern (attritjuted to lesions with a radial aspect), the reticular grey-blue regression pattern (coarse blue-grey net, with thick grey-blue lines and large holes, corresponding to white or pink regression areas) (10,11) and the aspeeific pattern, when none of the previous main patterns could be identified.…”
Section: Methodsmentioning
confidence: 99%
“…Several descriptors characterizing in situ and thin MMs have been proposed by the current study group, such as the dermoscopic island (9), reticular grey-blue regression (10,11) and peculiar network atypias (12). Moreover, classification into different melanoma subtypes enables the recognition of MM subpopulations that may not be immediately recognizable according to the established main dermoscopic patterns (7,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, the reticular grey-blue is the most common. 77 Other studies have also suggested various dermoscopic features that may be helpful in distinguishing MIS from other pigmented lesions.…”
Section: Clinical Features Key Pointsmentioning
confidence: 99%